Psikoedukasi Perencanaan Karir Memasuki Dunia Kerja pada Siswa Tingkat Akhir SMK Muhammadiyah 2 Bantul: Psychoeducation on Career Planning for Entering the World of Work for Final-Year Students of SMK Muhammadiyah 2 Bantul - Rahmadani, Khoirunnisa Rizki; Azizah, Debby Husna Nur; Budianti, Nur Rahmi; Ananda, Restu Patria; Aulia, Aulia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The problem of unemployment among vocational final-year students is an important issue that needs serious attention. Students at SMK Muhammadiyah 2 Bantul faced problems related to student career planning. Many students do not have a clear picture related to the continuation of their careers after graduating from school and are uncertain whether to continue to college or enter the world of work. In addition, other problems also arise due to the lack of real preparation to enter the world of work. Psychoeducation was conducted to make students aware of the importance of career planning and preparation. The method used was community development by involving 43 teachers and students. As a result of this activity, the students of SMK Muhammadiyah 2 Bantul were able to better understand themselves and determine their future career choices. In addition, students were also given an overview of the recruitment process and tips and tricks for facing job interviews. This activity will help students make informed decisions about education or careers and improve their knowledge.